STRATEGI PEMASARAN UBI KAYU NUABOSI DI DESA NDETUNDORA DI KECAMATAN ENDE, KABUPATEN ENDE - Maria Valentina Bagho Wea; Maria Bano; Ignatius Sinu (Buletin Ilmiah Impas, 2020)
The research has been conducted at Ndetundora 1 Village, Ende Sub- District, Ende Regency. The purpose of This research are to know: (1) Nuabosi cassava marketing strategy, (2) Nuabosi cassava marketing channel. (3) Cost, profit, margin, and farmer's share. This research was conducted in March 2019. The research method used was survey method with respondent interview techniques and questionnaires. Number of samples as many as 50 respondents. Determination of samples used in two stages namely first, what is done purposely (purposive sampling) and secondly which is simple random sampling. Data collected are primary data and secondary data. Primary data obtained from direct interview with farmers while secondary data obtained from institutions. Nuabosi's cassava marketing strategy, marketing channel, eco-disposal, cost, profit, margin, and farmer's share are quantitatively, qualitatively, and descriptive analysis. the research results show that (1) Marketing strategy using SWOT Analysis by finding strengthtens, weakness, opportunities, threats from products, promotions, places and prices. (2) Pattern of marketing channels namely farmers - traders of village retailers - consumers, farmers - village collector traders - city retailers - consumers, and at the last channel farmers - inter-island traders - consumers. The total cost to farmers for the first channel is Rp.400 / kg, the village retailer is Rp.1,587 / kg for margins. In this channel, the farmers are Rp. 5,000 / kg, the retailer is Rp.5.000. Farmers’s Share 71% and 100%. In the second channel, the total costs incurred by farmers are Rp. 12,500, village collectors are Rp. 15,000 / kg and city retailers are Rp. 20,000. Farmer marketing margin Rp 7,500, village collector traders rp 2,500 / kg, city retailer traders 5,000 / kg. And for the last channel the price of nuabosi cassava for farmers is Rp. 12,500 / kg and inter-island traders Rp. 25,000/kg. The total costs incurred are IDR 2,508 / kg, inter-island traders Rp 10,000. The margin on this channel is Rp. 12,500 / Kg and the collecting trader is Rp 12.500/kg. Farmer’s share for farmer is 50 %, while for inter-islan traders 100 %. Inter-islan traders 25.000 m